Design and Analysis of Biceps and Triceps Muscle Strengthening Structure - Vikas Malik, R. Ramakrishnan (International Journal of Advanced Science and Technology, 2020)
The field of sports engineering is a relatively new discipline of engineering. It connects two very different domains: engineering and sports. Engineers concerned with sports design build customized equipment related to a sportsperson’s needs and also measure the sportsperson’s performance, the equipment’s effectiveness, andanalyze how the two interact.Engineering, alongwith technology today,is playing akey role in not merelyenhancing the sportsperson’s performance, but in making fitnessmore safe andattractive. In this study, an exercise regimen is proposed for improving the strength of biceps and triceps of a sportsperson, followed by a proposed structure (equipment) for executing this regimen. The design of this structure is validated using theoretical calculations and simulations on ANSYS software.